2016
DOI: 10.1111/jfbc.12319
|View full text |Cite
|
Sign up to set email alerts
|

Preservation effect of high pressure processing on ascorbic acid of fruits and vegetables: A review

Abstract: High Pressure Processing (HPP) is a well‐established nonthermal technology for ensuring microbial safety and nutritional quality of foods. Ascorbic acid (AA) is highly labile antioxidant, susceptible to degradation when exposed to oxygen, change in pH, temperature, or pressure. Preservation of AA in fruit and vegetable products is a prime concern for food processors. This review summarizes recent data on the effect of HPP on AA content of different fruits and vegetables, and their products. In most of the food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 122 publications
(172 reference statements)
1
26
0
Order By: Relevance
“…Currently, HHP processing is a well-established non-thermal technology for increasing food safety and/or extending the shelf-life of refrigerated foods of high value (61). Products pasteurized by HHP processing show nutritional and organoleptic properties similar to those of the raw/fresh products, which is contrary to conventional thermal treatments (62, 63). Comparative studies on non-thermal preservation techniques reported that the effects of HHP on microbiological quality and physicochemical properties of juices were higher, or similar to, those observed with other non-thermal techniques, such as PEF (62).…”
Section: Non-thermal Stabilizationmentioning
confidence: 87%
“…Currently, HHP processing is a well-established non-thermal technology for increasing food safety and/or extending the shelf-life of refrigerated foods of high value (61). Products pasteurized by HHP processing show nutritional and organoleptic properties similar to those of the raw/fresh products, which is contrary to conventional thermal treatments (62, 63). Comparative studies on non-thermal preservation techniques reported that the effects of HHP on microbiological quality and physicochemical properties of juices were higher, or similar to, those observed with other non-thermal techniques, such as PEF (62).…”
Section: Non-thermal Stabilizationmentioning
confidence: 87%
“…The applied pressure can range from 200 to 900 MPa. The physical pressure compresses the product uniformly, which leads to a reduction in the number of microorganisms while keeping quality parameters unchanged; however, the minimum pressure required to inactivate vegetative microorganisms at ambient temperatures is 400 MPa [ 58 , 59 ]. The temperature used for HPP is usually below 40 °C, and the time used for the process ranges from a few minutes to an hour.…”
Section: Innovative Non-thermal Technologies In Fruit and Vegetabmentioning
confidence: 99%
“…The data compiled by Tewari and colleagues [ 59 ] shows that most of the conducted studies taking into account the impact of HPP on fruit and vegetable products resulted in a very high vitamin C retention (79–99% in fruit products and 67–93% in vegetable products). Additionally, it revealed better stability of vitamin C during the storage of pressure treated products compared to products after thermal treatment [ 57 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Innovative Non-thermal Technologies In Fruit and Vegetabmentioning
confidence: 99%
“…This was not consistent with the vitamin C content changes, suggesting that an increase in isothiocyanate content might not be related to changes in APX activity. Although the APX enzyme plays an important role in vitamin C metabolism, the measurable content of vitamin C in HPP processed fruits and vegetables is variable due to many possible mechanisms, such as the enhanced extraction of bioactive compounds and the cells’ rupture that releases their cytosol content, caused by the compression effect of the high pressure [ 41 ].…”
Section: Resultsmentioning
confidence: 99%